E-LIBRARY BERBASIS WEBSITE MENGGUNAKAN METODE ALGORITMA APRIORI DAN SEQUENTIAL SEARCH - Ibnu Muttaqin (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The library is one of the facilities in schools, universities or in the office and in the development of an increasingly advanced technology era and also libraries must follow technological developments that have begun to use e-libraries by reading e-books. For research in the case of the Putra Bangsa High School library, it does not have a digital library. In this study, SMA Putra Bangsa wants to create an E-library website for online reading. This study aims to search for books by implementing the Sequential Search method on the e-library application used to search for book data based on book titles, book categories and publishers which are array data 1 dimensions. In addition, to classify Putra Bangsa SMA data to find books that are recommended to website visitors by using the apriori algorithm method, this method determines the item set of the most popular books. So that this application allows readers to read efficiently and even read digital books through various devices that support browsing facilities using the internet